Impact of Common Reflecting and Absorbing Building Materials on THz Multipath Channels. Issue 2 (21st February 2022) - Gomez‐Ponce, Jorge; Abbasi, Naveed A.; Kondaveti, Revanth; Kumar, Ashish; Abu‐Surra, Shadi; Xu, Gary; Zhang, Charlie; Molisch, Andreas F.
Abstract: THz band communication has the potential to meet the high data rate demands of many current and future applications. However, before these networks are realized, extensive channel measurements are needed in order to characterize the wireless channel at these frequencies, in order to inform system design and deployment. In the current paper, we present a set of double‐directional channel measurements that are conducted in several relevant indoor and outdoor scenarios. Our aim is to see the effect of common building materials that might be particularly reflective or absorptive (such as energy‐saving glass, window blinds, or metallic reflectors), and how their presence changes the channel characteristics. Among other effects we find that ‐ depending on the considered dynamic range ‐ presence/absence of these materials can increase the required equalizer length by an order of magnitude. Key Points: Channel measurements for important THz scenarios is key toward their wider understanding The impact of some common materials on THz communication is presented by means of double‐directional measurements The aim is to see the effect of common building materials such as energy‐saving glass, window blinds, or metallic reflectors